A case report of successful treatment of abdominal pain with umbilicus visceral manipulation - Masoumeh Norouzi Allahleh Korabi; Assie Jokar; Marzieh Qaraaty (Golestan University Of Medical Sciences, 2024)
Background: Umbilicus visceral manipulation is an effective medical practice in the treatment of a wide range of diseases, including abdominal pain, as described in traditional Persian medicine (TPM) texts. Case description: A 35-year-old married female (G2P2Ab0L2NVD2) from Gorgan, Iran, presented to the TPM health care center affiliated with Golestan University of Medical Sciences on February 21, 2022, due to abdominal pain, obesity, and increased appetite. Conclusion: Tailoring the treatment to the individual characteristics of the client and incorporating TPM measures, such as manual procedures, in conjunction with modern medicine, can play a crucial role in the overall treatment process.